Unexpected Performance of a Bifunctional Sensitizer/Activator Component for Photon Energy Management via Upconversion - Antoniou, Giannis N.; Athanasopoulos, Stavros; Koyioni, Maria; Koutentis, Panayiotis A.; Keivanidis, Panagiotis E. (My University, 2024)
We here report on the observation of upconverted photoluminescence (UC-PL) from the blue-light-emitting 9,10-diphenylanthracene (DPA) mixed with the yellow-light-absorbing bifunctional sensitizer/activator component of (3,3,7,8,12,13,17,18-octaethylporphyrin-22,24-diid-2-one) PtII (PtOEP-K). Yellow-to-blue UC-PL (0.680 eV spectral upshift) is achieved at room temperature under ultralow power continuous incoherent photoexcitation (220 μW/cm2) despite the absence of triplet energy transfer (TET) between PtOEP-K and DPA. Under selective CW-laser photoexcitation of PtOEP-K in DPA:PtOEP-K, a 2.5% UC-PL quantum yield is obtained; that is an improvement exceeding by more than 3 orders of magnitude the UC-PL quantum yield of TTA-UC material combinations wherein no TET is operative. The PL response of DPA:PtOEP-K to varying laser fluence suggests that bimolecular annihilation reactions between triplet-excited PtOEP-K facilitate the UC-PL activation in DPA. These findings pave the way toward low-complexity strategies for the reduction of transmission losses in solar energy technologies through an innovative wavelength upshifting protocol involving excitonic materials.